Web Application Firewall With Telegram Bot Integration - Mohd Husny, Herny Ramadhani; Abdullah, Dalilah; Seid, Norsuhaili; Solaiman, Mohamad Amshar (Journal of Computing Technologies and Creative Content, 2017)
With the increasing trends of web-based attacks and successful hacks through vulnerability in web application, many organizations has turned to Web Application Firewall (WAF) as a countermeasure to secure their website from intruders. Despite its effectiveness, WAF is still subjected to advanced attack in which web administrators may need real-time attack notification in order to mitigate successfully. Apart from that, most enterprise level WAF on the market is expensive and feature administration interface that is complex to use (steep learning curve). Staffs need to be trained to handle these devices and that in turn add up to more cost. The project aim to provide solution for these problems by developing a WAF that can be managed through the Telegram chat interface. This enable administrator to receive real-time notification while an attack is ongoing and also makes management of the WAF less complex due to the simplistic interface of the Telegram client. As a plus, the resulting product is also more cost effective compared to most enterprise-level WAF on the market, thus this project is targeted for SME companies, which mostly run e-commerce websites. A SME company could save on resources while still be able to afford baseline security for their crucial web application, which may contain very sensitive financial information about their clients and the company itself.